2016
DOI: 10.1002/mats.201600046
|View full text |Cite
|
Sign up to set email alerts
|

Particle Nucleation in the Initial Stage of Emulsifier‐Free, Emulsion Organotellurium‐Mediated Living Radical Polymerization (Emulsion TERP) of Styrene: Kinetic Approach

Abstract: Kinetic simulations of polymer chain propagation in an aqueous medium in an initial stage of emulsifier‐free, emulsion organotellurium‐mediated living radical polymerization (emulsion TERP) of styrene with sodium poly(methacrylic acid)‐methyltellanyl (PMAA‐TeMe) as a control agent and 4,4′‐azobis(4‐cyanovaleric acid) as a water‐soluble azo‐initiator at various polymerization temperatures, which is carried out experimentally at pH > 9 in a previous article, is performed using PREDICI software from CiTGmbH. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The controlled generation of radicals is highly desirable in the subtle control of radical-related reactions in various fields, including radical polymerization, [1] catalysis, [2] and biomedical applications. [3] Thermal initiators are widely used as radical sources that can generate radicals under thermal stimuli.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…The controlled generation of radicals is highly desirable in the subtle control of radical-related reactions in various fields, including radical polymerization, [1] catalysis, [2] and biomedical applications. [3] Thermal initiators are widely used as radical sources that can generate radicals under thermal stimuli.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…As f value of BPO, 1.0 was used. Simulation for ITP of MMA based on the kinetic model was performed using PREDICI software from CiT GmbH (Rasfede, Germany) using kinetic coefficients shown in Table 1 , which are obtained from references shown in Table 2 . Concentrations of MMA, BPO and CHI 3 , which are, respectively, shown as [M], [I] and [CHI 3 ] in Table , used for the simulation are calculated from the recipe of the oil phase (except for PVA aqueous solution as the aqueous medium) of the ms ITP in the previous article: MMA, 5.0 g; BPO, 0.40 g; CHI 3 , 0.06 g (1 wt % PVA aqueous solution, 45.0 g).…”
Section: Model and Governing Equations Used For Bulk Itp And Bulk Crpmentioning
confidence: 99%
“…20 Cheng and Zhu's group reported that triphenylphosphine is an effective catalyst for RTCP, 24 while H-phosphonic acid derivatives have been used as RTCP catalysts by Vana et al 25 An advantage of RDRPs compared with other living polymerization systems, such as anionic and cationic polymerizations, is their high tolerance to water. Hence, the combination of RDRPs and aqueous heterogeneous polymerization systems (such as, miniemulsion, 13,[26][27][28][29][30][31] emulsion, [32][33][34][35][36][37] microemulsion, [38][39][40] and dispersion [41][42][43][44] polymerizations) provides well-defined polymers in particulate states. [45][46][47] Miniemulsion polymerization is an aqueous heterogeneous polymerization strategy involving the formation of monomer droplets in aqueous media prior to polymerization, where polymerization subsequently occurs; the monomer droplets function as nanocontainers for radical polymerization.…”
Section: Introductionmentioning
confidence: 99%